Post-Merger Integration: The Case Of Service Industry In China - Tian, Ye (2015)
This is a dissertation about merger and acquisition (M&A) integration of a high level industry in China, where M&As are becoming increasingly common and important. The history of failure of M&As also makes study of this phenomenon relevant. A review of existing literature identified a gap in research in high-level service industries. The study therefore has been undertaken of an integration case of high level service industry in China, asking how post-merger integration has been successfully conducted. Existing research suggested that there are six integration best practices, namely, culture and human due diligence, integration planning, strong integration manager, competence integration team, effective communication and high speed of integration process. In this qualitative study, the research confirmed five of the best practices as relevant to the successful integration of this company post merger. However, in a new finding the high speed of integration process, on the contrary, the result was opposite in the case, instead in this case the speed of integration was slow and integration process is incremental. As a result, three recommendations for practitioners are offered in the integration practice of high-level service practices offered, namely, accumulating before integration, minimizing disruption to frontlines and testing on the ground. It is recommended that further research be carried out.